Одержання бітумів і бітумних емульсій, модифікованих інден-кумароновими смолами - Гриценко, Юрій Борисович (Національний університет "Львівська політехніка", 2016)
Дисертаційна робота присвячена розробленню технологічних основ процесу одержання модифікованих бітумів і бітумних емульсій. Доведено, що для приготування модифікованих бітумів доцільно використовувати інден-кумаронову смолу з температурою розм’якшення 130-140 °С, яка одержується з вузької інден-кумаронової фракції (140-190 С) в присутності TiCl4 за наступних умов: температура – 37 °С, тривалість – 40 хв., концентрація каталізатора – 3,3 % мас. Внаслідок змішування інден-кумаронової смоли у кількості 7-12 % мас., пластифікаторів – 8-12 % мас. та дорожнього окисненого бітуму БДН 60/90 – 76-85 % мас. одержано товарний модифікований бітум марки БМП 60/90-52. Вибрано промисловий емульгатор “Redicote E 11”, використання якого дає змогу одержати товарну емульсію марки ЕКПМ-60 на основі бітуму, модифікованого ІКС. Показано, що модифіковані інден-кумароновою смолою бітумні емульсії можуть застосовуватися з метою створення тонкошарових дорожніх покриттів. На основі результатів експериментів запропоновано принципову технологічну схему одержання модифікованих бітумів і доведено доцільність її практичного використання у промисловості. Диссертация посвящена разработке технологических основ процесса получения модифицированных битумов и битумных эмульсий. Доказано, что для изготовления модифицированных битумов целесообразно использовать инден-кумароновую смолу с температурой размягчения 130-140°С, которая производится с использованием узкой инден-кумароновой фракции (140-190 0С) в присутствии TiCl4 при следующих условиях: температура – 37 ° С, продолжительность – 40 мин., концентрация катализатора – 3,3% масс. Вследствие смешивания инден-кумароновой смолы в количестве 7-12% масс., пластификаторов – 8-12% масс. и дорожного окисленного битума БДН 60/90 – 76-85% масс. получено товарный модифицированный битум марки БМП 60/90-52. Выбран промышленный эмульгатор «Redicote E 11», использование которого позволяет получить товарную эмульсию марки ЕКПМ-60 на основе битума, модифицированного ИКС. Показано, что модифицированные инден-кумароновой смолой битумные эмульсии могут применяться с целью приготовления тонкослойных дорожных покрытий. На основе результатов экспериментов предложено принципиальную технологическую схему получения модифицированных битумов и доказано целесообразность ее практического использования в промышленности. The work deals with the development of technological basis for the production of modified bitumen and bitumen emulsions. The procedure for the determination of adhesive properties of petroleum and modified bitumen under low temperatures was developed. The procedure allows to model binding agent behavior in the roadway at the temperatures below zero and their sharp changes. A series of modifiers were tested: industrial additives Elvaloy 4170 and Kraton D 1152; thermal polymerization petroleum resin; coumarone-indene resin which was synthesized at Lviv Polytechnic National University; petroleum carboxy-containing epoxy resin. Coumarone-indene resin (CIR) was found to be the best to improve the adhesive properties, including low-temperature ones. Its softening temperature was found to be above 130-140C. The effect of various parameters on CIR synthesis was determined. It was proposed to obtain CIR from the narrow coumarone-indene fraction (140-190C) in the presence of TiCl4 under the following conditions: temperature 37C, time 40 min., catalysts concentration 3.3 wt%. The effective activation energy of cooligomerization of indene-cumarene fraction (140–190C) has been determined in the presence of 3 wt % TiCl4 within the temperature range of 20–60 C and time interval of 5–40 min. It was found to be about 25 kJ/mol. Using the determined value it is possible to model CIR yield depending on process temperature and time. The commercial modified bitumen BMP 60/90-52 was obtained by mixing the coumarone-indene resin (softening temperature 135C, amount 7-12 wt%), plasticizers (residual extract after selective treatment or tar from West-Ukrainian oils, amount 8-12 wt%) and BDN 60/90 oxidated road bitumen (amount 76-85 wt%). The properties of obtained bitumen meet the requirements of the standard DSTU B V.2.7-135:2007. Bitumen emulsions (BE) were obtained using colloid mill. Redicote E 11 commercial emulsifier was used for the production of EKPM-60 emulsion (according to DSTU B V.2.7-129:2013) based on bitumen modified with CIR. The modified emulsions (unlike BE based on oxidated non-modified bitumen) may be used to produce high-quality thin-layer roadways. The experimental results were used for the development of technological flow chart and its advisability was validated. The effectiveness of the developed processes was proved by technical conditions for the production of modified bitumen pilot batch and certificate of proof in Lviv Polytechnic National University.
Получение битумов и битумных эмульсий, модифицированных инден-кумароновыми смолами
Production of bitumen and bitumen emulsions modified by coumarone-indene resins
Keywords: модифіковані бітуми; інден-кумаронова смола; бітумні емульсії; модифікатори; модифицированные битумы; инден-кумароновая смола; битумные эмульсии; модификаторы; modified bitumen; coumarone-indene resin; bitumen emulsion; modifiers